The Effect of Musculus Rhomboideus fibromyalgia Rehabilitation Program in Youth and Advance Freestyle and Greco – Roman Wrestlers - Abdul Zahraa, SAif; Farhan, Ahmed (Journal of Physical Education, 2022)
The research aimed at identifying the effect of rehabilitation program for musculus Rhomboideus suffering from chronic fibromyalgia in youth and advance freestyle and Greco roman wrestlers. The problem of the research lies in the lack of attention in rehabilitation program for this muscle. The community were (76) freestyle and Greco roman wrestlers suffering from fibromyalgia with (30) first degree injury, (25) second degree and (21) degree injuries. The subjects of the study were (13); (7) second degree, (6) third degree injury. Exercises were designed for rehabilitation that made 22 sessions with 6 – 12 exercises per session with medium to high intensity training. The results showed significant differences between pre and posttests in neck rotation to the left, right and degree of pain in favor of protested in the experimental group that used EMR (Electricity-Massage-Rubber Ropes) message and electro muscular stimulation.